Group early intervention eye movement desensitization and reprocessing therapy as a video-conference psychotherapy with frontline/emergency workers in response to the COVID-19 pandemic in the treatment of post-traumatic stress disorder and moral injury—An RCT study - Farrell, Derek; Moran, Johnny; Zat, Zeynep; Miller, Paul W.; Knibbs, Lorraine; Papanikolopoulos, Penny; Prattos, Tessa; McGowan, Iain; McLaughlin, Derek; Barron, Ian; Mattheß, Cordula; Kiernan, Matthew D. (Frontiers in Psychology, 2023)
Objective: Frontline mental health, emergency, law enforcement, and social workers have faced unprecedented psychological distress in responding to the Covid-19 pandemic. The purpose of the RCT (Randomised Controls Trial) study was to investigate the effectiveness of an intensive, early intervention, Group EMDR (Eye Movement Desensitisation and Reprocessing) therapy, delivered virtually, in treating Post-Traumatic Stress Disorder (PTSD) and Moral Injury using therapist rotation. Methods: The study’s design comprised a delayed (1-month) treatment intervention (control) versus an active group. Measurements included the International Trauma Questionnaire (ITQ), Generalised Anxiety Disorder Assessment (GAD-7), Patient Health Questionnaire (PHQ-9), Moral Injury Events Scale (MIES), and a Quality-of-Life psychometric (EQ-5D), tested at T0, T1: pre-treatment, T2: post-treatment, T3: 1-month follow-up (FU), T4: 3-month FU, and T5: 6-month FU. The Adverse Childhood Experiences – International version (ACEs) and Benevolent Childhood Experiences (BCEs) were ascertained at pre-treatment only. N=85 completed the study. Results: Results highlight a significant treatment effect within both active and control groups. Post Hoc comparisons of the ITQ demonstrated a significant difference between T1 pre (mean 36.8, SD 14.8) and T2 post (21.2, 15.1) (t11.58) = 15.68, p<.001). Further changes were also seen related to co-morbid factors. Post Hoc comparisons of the GAD-7 demonstrated significant difference between T1 pre (11.2, 4.91) and T2 post (6.49, 4.73)(t=6.22) = 4.41, p<.001; with significant difference also with the PHQ-9 between T1 pre (11.7, 5.68) and T2 post (6.64, 5.79)(t=6.30) = 3.95, p<.001, d = 0.71. The treatment effect occurred irrespective of either ACEs/BCEs during childhood. Moral Injury demonstrated no treatment effect between T1 pre and T5 6-month FU. The study’s findings discuss the impact of Group EMDR therapy delivered virtually, as a safe, relevant, effective, and efficient early intervention treatment. Conclusion: Treatment results demonstrate the effectiveness of the intervention as an intensive, virtual treatment intervention using therapist rotation. However, the moral dimensions of trauma need consideration for future research, intervention development, and potential for further scalability. The data contributes to the emerging literature on early trauma interventions.